Pengembangan Sistem Informasi Penjualan Jasa pada Bengkel Xyz - Hartono, Sugiarto (ComTech: Computer, Mathematics and Engineering Applications, 2014)
Information technology continues to evolve. For example in education, long time ago, people learned using stones. Advances in science and technology bring the community continue to improve the quality of life including technology itself. Bengkel XYZ is a company that sales service to customer especially in motorcycle reparation. The company is still using a file-based system. System development methodology used in this research is the Unified Process methodology using Object-Oriented approach. This research will result in a system design and application of sales system that can be used by the company to run day-to-day business operations, especially for the sales business process. By the design of information systems and the application of the sales system will integrate all data using centralized database, so that data redundancy can be reduced and the cost-effectiveness can be achieved.